Library Management System - Norhazifa Harum; Najwan Md Khambari; Norharyati Harum (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Manual library management requires a higher workforce for librarians and causes discrepancies during data encoding. The transaction history is too numerous and needs to be stored over a long period of time, requiring a lot of files for storage. With the advent of digital technology and the increasing complexity of library functions, traditional manual systems have become inefficient and time-consuming. In this work, an automated Library Management System (LMS) was developed specifically for education such as universities or colleges where users are students and admin to simplify the management of library resources, enhance accessibility, and improve overall efficiency. The system provides a user-friendly interface that enables librarians to quickly and accurately add, search, and update bibliographic information, ensuring a well-organized and easily searchable library collection. Also, it provides alternative methods for students to perform the borrowing process and check the current book availability at library through the system. The system also supports a range of user services, including patron registration, tracking borrowing history, and managing fines and penalties. The methodology used for this system is the Waterfall model, from the Software Development Life Cycle (SDLC). Overall, the LMS offers a comprehensive and efficient solution to address the challenges faced by modern libraries.